Noninvasive stereotactic radioablation for the treatment of atrial fibrillation: First‐in‐man experience. Issue 1 (3rd December 2019) - Qian, Pierre C.; Azpiri, Jose R.; Assad, Jose; Gonzales Aceves, Eric Noel; Cardona Ibarra, Carlos Erick; de la Pena, Cuauhtemoc; Hinojosa, Miguel; Wong, Doug; Fogarty, Thomas; Maguire, Patrick; Jack, Alice; Gardner, Edward A.; et al.
Abstract: Purpose: Catheter ablation is an effective therapy for atrial fibrillation (AF). However, risks remain, and improved efficacy is desired. Stereotactic body radiotherapy (SBRT) is a well‐established therapy used to noninvasively treat malignancies and functional disorders with precision. We evaluated the feasibility of stereotactic radioablation for treating paroxysmal AF. Methods: Two patients with drug‐refractory paroxysmal AF underwent pulmonary vein isolation with SBRT. After placement of a percutaneous active fixation temporary pacing lead tracking fiducial, computed tomography (CT) angiography was performed to define left atrial anatomy. A tailored planning treatment volume was created to deliver contiguous linear ablations to isolate the pulmonary veins and posterior wall. Patients were treated on an outpatient basis in the radioablation suite. Clinical follow‐up was performed through at least 24 months after therapy. Results: Both patients successfully underwent SBRT planning and treatment without significant early or long‐term side effects up to 48 months of follow‐up. One patient had AF recurrence after 6 months free of arrhythmia, while the second patient remains free of AF after 24 months with fibrosis detected on MRI scan consistent with the ablation lesion set. An incidentally noted small pericardial effusion occurred in one patient. Conclusion: Stereotactic radioablation may be feasible for the treatment of drug‐refractory AF. Further evaluation is warranted. Abstract : We evaluated the feasibility of stereotactic radioablation for treating paroxysmal atrial fibrillation. Two patients with drug‐refractory paroxysmal atrial fibrillation underwent pulmonary vein isolation with SBRT and followed for more than 24 months; one patient remained free of AF, with MRI findings consistent with left atrial fibrosis at ablation sites. We conclude that it is feasible to apply radioablation to the treatment of AF and further evaluation is warranted.